2019
DOI: 10.3390/rs11070803
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Quantitative Analysis of Tropospheric Impact on Inclined Geosynchronous SAR Imaging

Abstract: Geosynchronous orbit synthetic aperture radar (GEO SAR) has a long integration time and a large imaging scene. Therefore, various nonideal factors are easily accumulated, introducing phase errors and degrading the imaging quality. Within the long integration time, tropospheric status changes with time and space, which will result in image shifts and defocusing. According to the characteristics of GEO SAR, the modeling, and quantitative analysis of background troposphere and turbulence are conducted. For backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Therefore, GEO SAR has excellent potential in remote sensing, disaster management, marine monitoring, etc. Most GEO SAR research focuses on system design and optimization, resolution analysis, accurate imaging algorithms, and deformation retrieval [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GEO SAR has excellent potential in remote sensing, disaster management, marine monitoring, etc. Most GEO SAR research focuses on system design and optimization, resolution analysis, accurate imaging algorithms, and deformation retrieval [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…in 2017 with the Toolbox for Reducing Atmospheric InSAR Noise (TRAIN) [25] and in 2018 with GACOS [31], [43] or [26], [27]. In the broader context of geosynchronous synthetic aperture radar, troposphere and APS models are also proposed [44], [45], [46]. However, little is published recently on troposphere mitigation based on F) high resolution weather model data based on NWP.…”
Section: Introductionmentioning
confidence: 99%
“…These influences will increase in images with higher resolution and larger incidence angles [24]. [25] proposed a power spectrum model for modeling the turbulence random errors, showing the influence of the time-varying troposphere on radar imaging. [26] analyzed different types of temporal decorrelation and suggested that an advanced atmospheric model could provide wet delay prediction with a high precision based on a numerical model [27].…”
mentioning
confidence: 99%